Pemahaman Peta Konsep dan Miskonsepsi Siswa SMA Kelas X Semester 2 pada Materi Keanekaragaman Hayati - Indah Heriyanti Kartika Sari; Indah Sukmaning Asih; Lathifah Khoirunnisa; Hanna Rosmawati Juwita Tamherwarin; Zykka Berlian Rizkiani (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
This descriptive research is motivated by the many problems that arise due to the low competence of students' knowledge in learning Biology on Biodiversity material in grade 10 senior high school semester 2 which is closely related to misconceptions. This study aims to analyze concept maps and find out which sub-materials have the most misconceptions experienced by students in the subject of enriching life in grade 10 Semester 2 with material topics which include: the concept of biological conservation, diversity levels (genes, species and ecosystems). ), as well as the distribution of flora and fauna in Indonesia. This research is a qualitative descriptive study with the data collection technique that the author uses is to use literature studies from several sources related to the misconceptions of 10th grade high school students semester 2 on biodiversity material. Based on data obtained from several sources related to misconceptions experienced by students, where the most dominant sub-material students experience misconceptions is located on the concept of conserving biodiversity, conserving biodiversity at the level (genes, species and species), and sub-material trade and distribution of flora and fauna in Indonesia. The conclusion from the results of this study is a misconception of biodiversity material caused by differences in learning support reference books.